Efecto de la roturación del suelo con el hercules en el cultivo de banano - González Pereira, Ivonne Mercedes (2009)
In the interval of the weeks 39 at 52/07, in the Property of of property of Mr. Nelson Muñoz Custody, cultivated with banana tree of the Great Clone Cavendish, was carried out the breaking new ground study In situ from the floor to three distances of the son's base, 50, 60 and 70 cm, and a witness without breaking new ground to evaluate the goods, of this culture practice on the son's development until the production. The treatments were assigned to plants in number from 20 to each treatment, totaling 80 plants, following the limits of the Design Completely to modify. The analyzed they vary, to evaluate the treatments were: Diameter of the shaft, the son's Height, number of leaves for plant, number of hands for cluster, weight of the cluster in kg and grade of the fruit to the cut of the fruit. The variance analyses for the different variables to exception of the grade of the fruit, were significant, evidencing the kindness of the breaking new ground of the floor, with that which the truthfulness of Hypothesis was proven outlined for this investigation; also the ` it proves complementary of Duncan, to compare the averages they gave significant results. The breaking new ground of the floor zipped by the activity of the workers during the routine tasks of the handling of the cultivation, allowed a better to air penetration of the water, it causes that when perishing, it increases the activity of the alive part of the floor, microorganisms, worms, and other spineless ones that intervene in the decomposition of the matter organic and subsequent liberation of nutrients that I take advantage of them the roots of the plants. Of the treatments the breaking new ground to 60 cm gave the best results, in growth of the Shaft, plant height, reaching increments of and 10.35% in the increment of the weight of the cluster with relationship to the absolute witness. The variation coefficients were excellent for the drop less magnitude to 12%, that which evidences the control of the experiment error for the blockade of the treatments. The implementation costs were very economic since they didn't represent too much investment